Local Crowdsourcing for Annotating Audio: the Elevator Annotator platform - Karavellas, Themistoklis; Prameswari, Anggarda; Inel, Oana; de Boer, Victor (Human Computation, 2019)
Crowdsourcing and other human computation techniques have proven useful in collecting large numbers of annotations for various datasets. In the majority of cases, online platforms are used when running crowdsourcing campaigns. Local crowdsourcing is a variant where annotation is done on specific physical locations. This paper describes a local crowdsourcing concept, platform and experiment. The case setting concerns eliciting annotations for an audio archive. For the experiment, we developed a hardware platform designed to be deployed in building elevators. To evaluate the effectiveness of the platform and to test the influence of location on the annotation results, an experiment was set up in two different locations. In each location two different user interaction modalities are used. The results show that our simple local crowdsourcing setup is able to achieve acceptable accuracy levels with up to 4 annotations per hour, and that the location has a significant effect on accuracy.